Preventing Escape of Non-Native Species from Aquaculture Facilities in Florida, Part 1: General Considerations and Regulations - Quenton M. Tuckett; Carlos V. Martinez; Jared L. Ritch; Katelyn M. Lawson; Jeffrey E. Hill (EDIS)
Aquaculture is an important and diverse segment of the agricultural economy in Florida. Ornamental, live bait, food finfish, and other segments of this industry culture and trade in non-native species. Escape or release of these non-native cultured organisms is an environmental and legal concern in Florida and therefore a key consideration in aquaculture farm construction and operation. This 7-page fact sheet is the first in a four-part series devoted to educating industry and other stakeholders on the importance of preventing the escape of non-native species from aquaculture facilities, as well as strategies for non-native species containment and regulatory compliance. It introduces the series, explains why non-native species containment is important, provides information on regulations, including the Florida Aquaculture Best Management Practices rule, describes the BMP inspection process, and provides advice on achieving compliance with these important regulations. Written by Quenton M. Tuckett, Carlos V. Martinez, Jared L. Ritch, Katelyn M. Lawson, and Jeffrey E. Hill, and published by the School of Forest Resources and Conservation Program in Fisheries and Aquatic Sciences, August 2016.